On compactness and metrizability of nuclear spaces of manifolds - Ryazanov, V. I.; Рязанов, В. И.; Рязанов, В. И. (Institute of Mathematics, NAS of Ukraine, 1998)
We prove a theorem on the sequential compactness of the so-called nuclear space of an arbitrary topological manifold.